A randomized phase II study of SM‐88 plus methoxsalen, phenytoin, and sirolimus in patients with metastatic pancreatic cancer treated in the second line and beyond. (2nd May 2022) - Noel, Marcus S.; Kim, Semmie; Hartley, Marion L.; Wong, Steve; Picozzi, Vincent J.; Staszewski, Harry; Kim, Dae Won; Van Tornout, Jan M.; Philip, Philip Agop; Chung, Vincent; Ocean, Allyson J.; Wang‐Gillam, Andrea
Abstract: Background: This trial explores SM‐88 used with methoxsalen, phenytoin, and sirolimus (MPS) in pretreated metastatic pancreatic ductal adenocarcinoma (mPDAC) Methods: Forty‐nine patients were randomized to daily 460 or 920 mg oral SM‐88 with MPS (SM‐88 Regimen). The primary endpoint was objective response rate (RECIST 1.1). Results: Thirty‐seven patients completed ≥ one cycle of SM‐88 Regimen (response evaluable population). Disease control rate (DCR), overall survival (OS), and progression‐free survival (PFS) did not differ significantly between dose levels. Stable disease was achieved in 9/37 patients (DCR, 24.3%); there were no complete or partial responses. Quality‐of‐life (QOL) was maintained and trended in favor of 920 mg. SM‐88 Regimen was well tolerated; a single patient (1/49) had related grade 3 and 4 adverse events, which later resolved. In the intention‐to‐treat population of 49 patients, the median overall survival (mOS) was 3.4 months (95% CI: 2.7–4.9 months). Those treated in the second line had an mOS of 8.1 months and a median PFS of 3.8 months. Survival was higher for patients with stable versus progressive disease (any line; mOS: 10.6 months vs. 3.9 months; p = 0.01). Conclusions: SM‐88 Regimen has a favorable safety profile with encouraging QOL effects, disease control, and survival trends. This regimen should be explored in the second‐line treatment of patients with mPDAC. ClinicalTrials.gov Identifier: NCT03512756. Abstract : This trial explores 460 or 920 mg oral SM‐88 daily, used with methoxsalen, phenytoin, and sirolimus (MPS) in previously treated patients with metastatic pancreatic ductal adenocarcinoma (mPDAC). SM‐88 + MPS was well tolerated (1 of 49 patients had drug‐related grade 3/4 adverse events), patient quality‐of‐life was maintained, and overall survival trended toward being better for patients treated in the second (median overall survival [mOS], 8.1 months; median progression‐free survival [mPFS], 3.8 months) versus ≥ third line (mOS, 3.7 months; mPFS, 1.8 months). SM‐88 + MPS should be further explored in the second‐line treatment of patients with mPDAC.